Pengaruh Ketepatan Waktu Pengiriman dan Kualitas Layanan Terhadap Keputusan Pembelian di Aplikasi Shopee - Mahdani, Imam; Wahono, Budi; Rahman, Fahrurrozi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract Nowadays, with increasingly rapid technological developments, one of the impacts is that purchases are becoming faster and more rapid through online markets.This study investigates the relationship between punctuality(on-time delivery) and quality of service with purchasing decisions on one of the online markets, namely Shopee. This study conducted on students of the Islamic University of Malang. The research variables consist of On-time Delivery (X1) and Quality (X2) as independent variables and Purchasing decisions (Y) as the dependent variable. In this study, it was found that there was a simultaneous influence between the variables of On-Time Delivery and Service Quality on Purchasing Decisions. Even if separated, the variable of On-Time Delivery has a significant positive effect on Purchasing Decisions and the variable of Service Quality has a significant positive effect on Purchasing Decisions. Keywords: On-time delivery, punctuality, quality of service, partial regression, simultaneous regression